Qira’at sebagai Perangkat Hermeneutik dalam Literatur Tafsir Indonesia - Mutmainah Mutmainah; Romlah Widayati; Said Agil Husin Al-Munawar; Ahmad Syaifuddin Amin (SUHUF, 2026)
Abstract This study examines the quality and classification of qiraʾat variants in Indonesian Qur’anic exegetical literature, with particular attention to the use of qira’at varieties in the interpretation of surah al-Baqarah. The study is premised on the observation that the use of qiraʾat in the Indonesian exegetical tradition has generally emphasized interpretive and semantic functions rather than rigorous sanad-based verification of recitational authority. Using a library research approach, this article applies descriptive-analytical and comparative methods to five Indonesian tafsir works from different historical periods: Tarjuman al-Mustafid, Tafsir al-Munir (Marah Labid), Maljaʾ at-Talibin, Tafsir al-Mishbah, and Firdaus an-Naʿim. The data were analyzed through the identification, classification, and comparison of qiraʾat variants based on their status as mutawatir or syazzah, as well as the ways in which they are presented within each tafsir. The findings reveal that mutawatir qiraʾat constitute the principal foundation across all examined commentaries, although several mufassirs also incorporate qira’at syazzah readings for linguistic, juridical, and semantic purposes. Maljaʾ at-Talibin is the most consistent in restricting itself to mutawatir readings, whereas the other tafsirs combine both categories to varying degrees. This study demonstrates that qiraʾat in the Indonesian tafsir tradition function not only as recitational variants, but also as hermeneutical instruments reflecting both the continuity of the wider Islamic intellectual tradition and the distinctive characteristics of Indonesian Qur’anic scholarship.